PENCIPTAAN BUKU ILUSTRASI TARI TOPENG PANJI MALANGAN UNTUK MEMPOPULERKAN BUDAYA TRADISIONAL KOTA MALANG KEPADA REMAJA - Ghozali, Moh Afrizal; Fianto, Achmad Yanu Alif; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2015)
Abstract:The aim of this study is to provide education about the traditional culture of the city of Malang to adolescents. Introducing traditional art flag Malang Mask Dance in the wider community, especially teenagers. The study was conducted using qualitative research method is by conducting interviews, observation, documentation, and literature to obtain the data used to support the manufacture of the design concept of branding. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to creative planning to reach the intended target audience. After analyzing the data, found a concept or keyword creation illustrated book is "The depiction of ideals". Description of the concept of "The depiction of ideals" is a form of the meaning of role model for teens inconsistent in attitude, the intent of this keyword is expected that adolescents know traditional dance mask dance Panji Malangan and able to preserve and imitate the good values that exist in the mask dance Panji Malangan, so that teens can get to know the art of traditional culture, understand the meaning and values as well as preserving the traditional culture such as dance masks flag Malangan. Results of the creation of this illustrated book is to popularize the traditional culture of the city of Malang to adolescents.Â Keywords:Illustrated, Mask Dance, Traditional Culture, Adolescents.